Integrated Analysis of Sustainable Marketing Research with Bibliometric Insights and Theoretical Framework Development - Prasetya, Prita; Najib, Mukhamad (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
The purpose of this study is to develop a conceptual framework for sustainable marketing by conducting a bibliometric analysis to identify publication trends, and key research themes in the field of sustainable marketing. Bibliometric methods were used to analyze 351 articles indexed in Scopus, using VOSviewer for visualization. The data screening process followed the PRISMA protocol, focusing on journal articles written in English. Keyword co-occurrence and cluster analysis were used to identify research themes. The findings show a significant increase in publications on sustainable marketing since 2018, with six major research clusters. The research proposes an integrative framework for advancing sustainable marketing strategies across different regional and global contexts. It was limited to the Scopus database and focused on bibliometric analysis without integrating qualitative insights from other literature reviews. Future research could build on the proposed framework to address regional variations in sustainable marketing practices. The findings can provide valuable insights for marketers, policy makers and researchers to improve sustainable marketing strategies. The proposed framework can guide businesses in promoting sustainable consumption and policymakers in shaping ecosystems that support sustainability. It also offers theoretical and practical contributions to the literature on sustainable marketing.